2021
DOI: 10.3390/ijms222413254
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive, Basal, and β-Alanine-Mediated Activation of the Human Mas-Related G Protein-Coupled Receptor D Induces Release of the Inflammatory Cytokine IL-6 and Is Dependent on NF-κB Signaling

Abstract: G protein-coupled receptors (GPCRs) have emerged as key players in regulating (patho)physiological processes, including inflammation. Members of the Mas-related G protein coupled receptors (MRGPRs), a subfamily of GPCRs, are largely expressed by sensory neurons and known to modulate itch and pain. Several members of MRGPRs are also expressed in mast cells, macrophages, and in cardiovascular tissue, linking them to pseudo-allergic drug reactions and suggesting a pivotal role in the cardiovascular system. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11060953/s1, Figure S1: The inhibitors employed in main Figure 1 exert no cytotoxicity on cultured skin MC; Figure S2: MC degranulation via MRGPRX2 relies on Gαi, Gαq and calcium mobilization as evidenced by histamine release; Figure S3: The survival of ex vivo skin MC is not perceptibly compromised by the inhibitors employed in main Figure 1; Figure S4: Differences between c48/80 and SP from main Figure 1; Figure S5: Comparison between cultured and ex vivo skin MCs from main Figure 1; Figure S6: The inhibitors employed in main Figure 2 exert no cytotoxicity on cultured skin MC; Figure S7: The survival of ex vivo skin MCs is not perceptibly compromised by the inhibitors employed in main Figure 2; Figure S8: Differences between c48/80 and SP from main Figure 2; S1: Inhibitors employed and their primary targets. References [15,30,31,33,36,38,39,44,49,51,55,[60][61][62][86][87][88][89][90][91][92][93][94][95][96] are cited in the Supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11060953/s1, Figure S1: The inhibitors employed in main Figure 1 exert no cytotoxicity on cultured skin MC; Figure S2: MC degranulation via MRGPRX2 relies on Gαi, Gαq and calcium mobilization as evidenced by histamine release; Figure S3: The survival of ex vivo skin MC is not perceptibly compromised by the inhibitors employed in main Figure 1; Figure S4: Differences between c48/80 and SP from main Figure 1; Figure S5: Comparison between cultured and ex vivo skin MCs from main Figure 1; Figure S6: The inhibitors employed in main Figure 2 exert no cytotoxicity on cultured skin MC; Figure S7: The survival of ex vivo skin MCs is not perceptibly compromised by the inhibitors employed in main Figure 2; Figure S8: Differences between c48/80 and SP from main Figure 2; S1: Inhibitors employed and their primary targets. References [15,30,31,33,36,38,39,44,49,51,55,[60][61][62][86][87][88][89][90][91][92][93][94][95][96] are cited in the Supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“… 33 IL‐1β is one of these pro‐inflammatory factors to activate NF‐κB. The activation of NF‐κB upregulates the release of IL‐1β, IL‐6, 42 and tumor necrosis factor‐α (TNF‐α), 43 which fuels apoptosis 44 , 45 and inflammation. 46 , 47 ROS activated by IL‐1β is another pro‐inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that human podocytes express MRGPRD, the expression of which increased upon extracellular L-BAIBA supplementation. MRGPRD belongs to Mas-related G protein-coupled receptors and has been mostly associated with neuronal excitability and the sensation of pain and itch 20 . MRGPRD was first discovered in sensory neurons of the mouse dorsal root ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression was subsequently found in other organs and tissues, including arteries, testes, the urinary bladder, adipose tissue, and the gastrointestinal tract 21 . Although β-alanine is the best known MRGPRD ligand, it can also be stimulated by other molecules, such as alamandine 22 , angiotensin II 20 , and L-BAIBA 15 . The downstream effects of MRGPRD activation are multidirectional.…”
Section: Discussionmentioning
confidence: 99%